Hemodialysis for the treatment of dabigatran‐associated bleeding: a case report and systematic review. (29th September 2015) - Chai‐Adisaksopha, C.; Hillis, C.; Lim, W.; Boonyawat, K.; Moffat, K.; Crowther, M.
Summary Background Dabigatran, a direct thrombin inhibitor, is effective for the treatment of venous thromboembolism and the prevention of stroke and systemic embolism resulting from atrial fibrillation. The most effective way of reversing the anticoagulant effect of dabigatran in patients who have bleeding complications is unknown. Objectives To document the clinical outcomes of patients undergoing renal replacement therapy (RRT) for dabigatran‐associated bleeding. Methods We searched MEDLINE and EMBASE up to May 2015. Articles were selected if the patients presented with dabigatran‐associated bleeding, underwent RRT for dabigatran removal, and reported an effect on bleeding. Results The search yielded 22 studies representing 35 unique patient cases. The median patient age was 74.1 years (range, 56–94 years). Thirteen patients (37.1%) were female, and 32 (91.4%) patients received dabigatran for atrial fibrillation. Twenty‐three patients (65.7%) underwent intermittent hemodialysis, 10 patients (28.6%) underwent continuous RRT (CRRT), and two patients underwent both intermittent hemodialysis and CRRT. Following RRT, there were significant reductions in dabigatran concentrations (P = 0.001). Rebound of the dabigatran concentration was reported in 12 (57.1%) patients following cessation of RRT. Hemostasis was reportedly achieved in 24 patients (70.6%), and 10 patients (29.4%) died because of bleeding. Conclusions In patients with dabigatran‐associated bleeding, RRT appears to be effective in reducing dabigatran concentrations, and in case reports this has been associated with a reduction in the duration and/or severity of bleeding. However, a rebound in concentrations may be seen following withdrawal of RRT, suggesting that a prolonged course of RRT may be more effective.